Exercise targeted at the level of maximal lipid oxidation (LIPOXmax) improves weight loss, decreases orexigenic pulsions and increases satiety after sleeve gastrectomy - Jean-Frédéric Brun; Valentin Lasteyrie; Lylia Hammoudi; David Nocca; Edouard Ghanassia; Philippe Noirez; Constance Chevalier; Jacques Mercier; Eric Raynaud de Mauverger (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2019)
Background and Purpose: Sleeve gastrectomy is a major therapy of morbid obesity, but recent reports suggest that its effects on weight loss are improved when patients increase their muscular activity, while a weight regain may occur in more than 30% of patients after 40 months. Exercise is an effective mean of preventing weight regain. In a recent preliminary study, we reported that exercise training targeted at the level of maximal lipid oxidation (LIPOXmax) improved weight loss and weight stabilization at 30 months. This study extends this previous one and aims at describing the kinetics of weight loss on 60 months after sleeve in people performing or not a LIPOXmax training and to see whether this variety of training exerts a satietogenic effect in sleeve patientsas has been evidenced in nonoperated obese subjects.